Konsep Hijrah dalam Al-Tafsir Al-Munir - Zuhairi, Faris; Sulthoni, Akhmad; Romadlon, Arif Firdausi Nur (STAINI Press, 2024)
In the phenomenon of hijrah among public figures via social media, this action attracts attention and has an impact on appearance and consumer behavior. Hijrah is considered an act of faith that reflects indifference to the world in order to achieve piety. The event of the Hijrah of the Prophet Muhammad. and the meaning of the word